Effect of Si content on the microstructure and properties of Al–Si alloys fabricated using hot extrusion. Issue 11 (3rd April 2017) - Ma, Pan; Jia, Yandong; Prashanth, Konda Gokuidoss; Yu, Zhishui; Li, Chonggui; Zhao, Jian; Yang, Shanglei; Huang, Lixin
Abstract: Abstract : Al–(12, 20, 35 wt%)Si alloys were fabricated using powder metallurgy process involving hot pressing followed by hot extrusion. The effect of Si content on the microstructure [by scanning electron microscopy], the mechanical properties (hardness and tensile tests), and the thermal expansion behavior were studied in detail, respectively. Due to the friction between the Si phase and the matrix, as well as the diffusion of the Si atoms, the Si phase becomes a particulate shape after hot extrusion, and the size increases with increasing Si content. The mechanical strength increases, whereas, the elongation decreases with increasing the Si content from 12 to 35 wt%, which lead to a variation of the fracture mechanism from ductile to brittle failure. The coefficient of thermal expansion (CTE) decreases with increasing Si content as a result of restriction of Si on the Al matrix, and the measured CTE value is in good agreement with the Turner model below 573 K.